2002
DOI: 10.1177/1077727x02031001003
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' Clothing Purchase Motivations, Information Sources, and Store Selection Criteria: A Comparison of Male/Female and Impulse/Nonimpulse Shoppers

Abstract: The purpose of this study was to examine high school adolescents' clothing shopping frequency, expenditure, purchase motivations, information sources, and store selection criteria and to determine the similarities and differences between male and female as well as impulse and nonimpulse shoppers. A survey design was used to collect the data. One hundred thirty‐seven high school students, in 9th to 12th grade, 69 males and 68 females, were recruited. Similarities were found between male and female participants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
2
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 28 publications
5
63
2
5
Order By: Relevance
“…Many studies in the literature confirmed the effect of consumers' benefit perceptions on online shopping intention (Chen-Yu and Seock, 2002;Szymanski and Hise, 2000). Based on the findings in the current literature and the classifications of perceived benefit types in this context, we propose the following hypothesizes:…”
Section: Proposed Research Model and Hypothesismentioning
confidence: 66%
“…Many studies in the literature confirmed the effect of consumers' benefit perceptions on online shopping intention (Chen-Yu and Seock, 2002;Szymanski and Hise, 2000). Based on the findings in the current literature and the classifications of perceived benefit types in this context, we propose the following hypothesizes:…”
Section: Proposed Research Model and Hypothesismentioning
confidence: 66%
“…The first section was used to determine the respondents' perceived importance of apparel retail store environmental cues. Fourteen items were used to measure respondents' indication of the relative importance of apparel retail store environmental attributes, which were adapted from previous studies (Chen-Yu and Seock, 2002;Eckman et al, 1990;Louviere, 1984;Pan and Zinkhan, 2006). They were measured with a 4-point Likert-type scale ranging from not important at all (1) to very important (4).…”
Section: Instrumentmentioning
confidence: 99%
“…these studies have recommended similar studies to be carried out on the male shoppers (Bellenger & Korgaonkar, 1980;Du Preez, 2003;Muzinich, Pecotich & Putrevu, 2003). It is noted that there has been scant research concentrated on males and gender differences in the area of consumer behavior (Chen-Yu & Seock, 2002). Shopper typologies research in pertinent to different shopping styles for men and women has gained its popularity recently (Bakewell & Vincent-Wayne, 2004;Dholakia & Chiang, 2003;Otnes & McGrath, 2001).…”
Section: Introductionmentioning
confidence: 99%